Mekanisme dan Implementasi Pembiayaan KPR BTN Platinum iB dengan Akad Musyarakah Mutanaqisah di Bank BTN Syariah KCPS Kudus - Nirmala Amelia Husein; Miswan Ansori (CV. ULIL ALBAB CORP, 2024)
This study examines the mechanism and implementation of KPR BTN Platinum iB financing with the Musyarakah Mutanaqisah contract at Bank BTN Syariah KCPS Kudus. Using a qualitative method with a case study approach, this research explores the application process, requirements, financing analysis, and contract implementation. The results show that Bank BTN Syariah KCPS Kudus has disbursed mortgage financing to 442 customers from January 2022 to September 2024, with 25 customers using Non-Subsidized KPR products. The financing process includes document submission, analysis using the 5C principles, and the Musyarakah Mutanaqisah contract. The implementation of this contract complies with DSN-MUI Fatwa No. 73/DSN-MUI/XI/2008, where the bank and customer act as partners in asset ownership. The study concludes that KPR BTN Platinum iB financing with the Musyarakah Mutanaqisah contract has been implemented in accordance with sharia principles and provides a more flexible home financing alternative for the community. Keywoards : Islamic Mortgage Financing, Musyarakah Mutanaqisah (MMQ) Contract, Islamic Banking